Effect Of Fullerene (C60) Concentration In Pectin Polysaccharide Thin Film For Resistive Switching Characterization - Cheong, Yi Huan (Universiti Sains Malaysia, 2022)
The rapidly growing electronic waste had become one of the major global issues in the electronic eras. Resistive switching is one of the most promising memory technologies due to its high storage density, simple structure, and low power consumption. The biocompatible pectin extracted from citrus peel had been introduced to be fabricated as the insulating layer of the Resistive Random Access Memory (RRAM) devices which exhibits excellent resistive switching characteristics. However, it is insufficient to beat the conventional inorganic materials. It is discovered that fullerene (C60) had improved the endurance and retention stability of the RRAM devices due to its electron-accepting nature. Herein, different concentrations of C60 were be blended with pectin to fabricate RRAM devices (Au-Pd/pectin-C60/indium tin oxides (ITO)) to see the effects. Wettability test had been conducted by using goniometer to determine the surface tension of pectin-C60 liquid precursors and the contact angle of the precursor with ITO surface, surface roughness observed and determined by using the Atomic Force Microscopy (AFM), Fourrier Transform Infra-Red (FTIR) spectroscopy to determine the functional groups and the electronic properties by using Semiconductor Parameter Analyzer (SPA). Addition of C60 into the pectin precursors had decreased the wettability of the precursors and caused the thin films surface roughness to increase. The devices exhibit good ON/OFF ratio (>10), the addition of C60 reduces the Vset values, lower energy is required to operate the devices. Furthermore, it had reduced the read memory window. This study thus provides a comprehensive comparison of the physical and electronic behavior of the pectin-based RRAM devices after the addition of C60 into the thin film. Although C60 had caused the downgrade of RRAM devices, it still holds promise for potential applications for NVM devices.